It's time to revise the role of positive D- penicillamine challenge test in diagnosis of Wilson disease - karbasian, fereshteh; Hosseini, Amirhossein; Dara, Naghi; Javdani Yekta, Sarah; Imanzadeh, Negar; Sayyari, Aliakbar (Student Research in Translational Medicine, 2020)
Hepatic involvement in Wilson disease consists of isolated elevated liver enzyme, asymptomatic hepatomegaly, cirrhosis and acute liver failure. Here, we report three patients with unexplained elevated liver enzymes. By considering the level of urinary excretion of copper after penicillamine challenge test, we had some problems in the process of diagnosis. Therefore, we thought of cautiously applying the diagnostic cut-off in the mentioned challenge test